Myostatin inhibitors as pharmacological treatment for muscle wasting and muscular dystrophy. Issue 1 (1st January 2017) - Saitoh, Masakazu; Ishida, Junichi; Ebner, Nicole; Anker, Stefan D.; Springer, Jochen; von Haehling, Stephan
Abstract: Myostatin, a member of the transforming growth factor beta (TGF‐β) superfamily that is highly expressed in skeletal muscle, was first described in 1997. It has been known that loss of myostatin function induces an increase in muscle mass in mice, cow, dogs and humans. Therefore, myostatin and its receptor have emerged as a therapeutic target for loss of skeletal muscle such as sarcopenia and cachexia, as well as muscular dystrophies. At the molecular level, myostatin binds to and activates the activin receptor IIB (ActRIIB)/Alk 4/5 complex. Therapeutic approaches therefore are being taken both pre‐clinically and clinically to inhibit the myostatin signaling pathway. Several myostatin inhibitors, including myostatin antibodies, anti‐myostatin peptibody, activin A antibody, soluble (decoy) forms of ActRIIB (ActR II B‐Fc), anti‐myostatin adnectin, ActR II B antibody have been tested in the last decade. The aim of this review is to present the current knowledge of several myostatin inhibitors as a therapeutic approach for patients with loss of skeletal muscle.